2010
DOI: 10.1016/j.addbeh.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric distress, risk behavior, and treatment enrollment among syringe exchange participants

Abstract: The present study evaluated psychiatric distress as a predictor of treatment enrollment in out-oftreatment injection opioid users newly registered at the Baltimore Needle Exchange Program (BNEP). Study participants (n = 281) completed the Addiction Severity Index (ASI), the Risk Assessment Battery (RAB), and the Symptom Checklist-90 (SCL-90-R), and were randomly assigned to one of three different conditions for 4-months that evaluated referral strategies designed to promote treatment interest and enrollment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Patients that used injected drugs exhibited higher rates of mental distress, consistent with previous findings [52]. This finding suggested that the severity of a SUD was related to the level of mental distress.…”
Section: Discussionsupporting
confidence: 91%
“…Patients that used injected drugs exhibited higher rates of mental distress, consistent with previous findings [52]. This finding suggested that the severity of a SUD was related to the level of mental distress.…”
Section: Discussionsupporting
confidence: 91%
“…The possibility that PTSD and traumatic event exposure could be associated with drug abuse treatment‐seeking follows from the considerable evidence supporting a connection between PTSD and higher rates of medical and psychiatric treatment‐seeking , and between generalized psychiatric distress and drug abuse treatment‐seeking . Injecting drug users who report that the extreme negative consequences of their drug use have prompted their desire for treatment are popularly said to have hit ‘rock bottom’ , which can be associated with sustained remission .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies with methadone maintenance or other drug treatment patients (Camacho, et al, 1996; Kleinman, et al, 1994; Malow, et al, 1992; Metzger, et al, 1991; Perdue, et al, 2003; Pilowsky, et al, 2011; Woody, et al, 1997), and drug users not in treatment (Johnson, et al, 2003; Johnson, et al, 2002; Simpson, et al, 1993; Strathdee, et al, 1997), including syringe exchange program participants (Kidorf, et al, 2010), have found that symptoms of psychological distress or dysfunction, particularly symptoms of depression, are associated with injection risk behavior, including sharing syringes and other equipment, number of sharing partners, sharing with strangers, and sharing with a person known to be HIV-positive.…”
mentioning
confidence: 99%